Do crude oil prices drive the relationship between stock markets of oil-importing and oil-exporting countries? - Manel Youssegf; Khaled Mokni (Economies, 2019)
The impact that oil market shocks have on stock markets of oil-related economies has several implications for both domestic and foreign investors. Thus, we investigate the role of the oil market in deriving the dynamic linkage between stock markets of oil-exporting and oil-importing countries. We employed a DCC-FIGARCH model to assess the dynamic relationship between these markets over the period between 2000 and 2018. Our findings report the following regularities: First, the oil-stock markets' relationship and that between oil-importing and oil-exporting countries' stock markets themselves is time-varying. Moreover, we note that the response of stock market returns to oil price changes in oil-importing countries changes is more pronounced than for oil-exporting countries during periods of turmoil. Second, the oil-stock dynamic correlations tend to change as a result of the origin of oil prices shocks stemming from the period of global turmoil or changes in the global business cycle. Third, oil prices significantly drive the relationship between oil-importing and oil-exporting countries' stock markets in both high and low oil-stock correlation regimes.
Keywords: C32; C51; G15; Q40; 330; oil prices; dynamic conditional correlations; oil-exporting countries; oil-importing countries; stock markets